Global longitudinal strain and left ventricular ejection fraction for early detection of chemotherapy-related cardiac dysfunction in breast cancer: A prospective comparison of doxorubicin-based and paclitaxel–carboplatin regimens - Faradilla, Rizka; Heriansyah, Teuku; Novita, Novita; Munirwan, Haris; Fitra, Maha (Narra Sains Indonesia, 2026)
Left ventricular ejection fraction (LVEF) is widely used in routine practice to assess cardiotoxicity; however, reductions in LVEF often reflect relatively advanced myocardial damage. Global longitudinal strain (GLS) quantifies myocardial deformation and has demonstrated greater sensitivity for identifying early systolic dysfunction, yet comparative evidence on myocardial strain changes between doxorubicin-based regimens and non-anthracycline chemotherapy in breast cancer patients remains limited. The aim of this study was to compare changes in left ventricular GLS and LVEF between breast cancer patients receiving doxorubicin-based chemotherapy and those treated with paclitaxel–carboplatin regimens. A prospective cohort study was conducted among 106 women with histopathologically confirmed breast cancer, who were allocated to receive either a doxorubicin-based regimen (n=53) or a paclitaxel–carboplatin regimen (n=53). Transthoracic echocardiography was performed within seven days before chemotherapy initiation and repeated after four months. Left ventricular GLS was measured using two-dimensional speckle-tracking echocardiography from apical views and analyzed offline using the 17-segment model. Baseline GLS values did not differ significantly between the doxorubicin and paclitaxel–carboplatin groups (−20.47±0.45 vs −20.38±0.53; p=0.410). After four months, GLS was significantly reduced in the doxorubicin group compared with the paclitaxel–carboplatin group (−15.04±0.35 vs −19.54±0.50; p<0.001). The change in GLS (ΔGLS) was also greater in the doxorubicin group (5.43±0.12 vs 0.84±0.11; p<0.001). No significant differences were observed in LVEF before chemotherapy (55.26±1.78 vs 55.39±1.99; p=0.720), after chemotherapy (51.32±1.51 vs 51.60±1.64; p=0.359), or in ΔLVEF (p=0.484). In conclusion, doxorubicin-based chemotherapy was associated with early subclinical systolic dysfunction detectable by GLS before measurable LVEF decline, whereas paclitaxel–carboplatin was associated with relatively preserved myocardial deformation. These findings support the incorporation of strain imaging into routine cardiac surveillance for earlier identification and management of chemotherapy-related myocardial injury.